2012
DOI: 10.1016/j.amjcard.2012.04.051
|View full text |Cite
|
Sign up to set email alerts
|

β Blockers for Prevention of Exercise-Induced Left Ventricular Outflow Tract Obstruction in Patients With Hypertrophic Cardiomyopathy

Abstract: Whether treatment with β blockers (BBs) is of benefit to patients with hypertrophic cardiomyopathy (HC) and provocable outflow obstruction (with none or with only mild heart failure symptoms) is largely unresolved. Thus, we prospectively studied 27 patients with HC (age 36 ± 15 years; 81% men) with New York Heart Association class I or II, without obstruction at rest, but with exercise-induced left ventricular outflow tract (LVOT) gradient of ≥ 30 mm Hg. Patients underwent exercise echocardiography at baseline… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
40
0
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 80 publications
(45 citation statements)
references
References 19 publications
0
40
0
5
Order By: Relevance
“…Beta adrenergic receptor blockers, without intrinsic sympathetic activity, were first used in the treatment of HCM in the 1960s 227229 , and have, since then, remained the cornerstone of pharmacological treatment of symptomatic patients. They are effective in the relief of ischemic chest discomfort and may attenuate exercise-induced LVOT obstruction and resulting dyspnea as well 230 .…”
Section: Managementmentioning
confidence: 99%
“…Beta adrenergic receptor blockers, without intrinsic sympathetic activity, were first used in the treatment of HCM in the 1960s 227229 , and have, since then, remained the cornerstone of pharmacological treatment of symptomatic patients. They are effective in the relief of ischemic chest discomfort and may attenuate exercise-induced LVOT obstruction and resulting dyspnea as well 230 .…”
Section: Managementmentioning
confidence: 99%
“…In fact, Nistri et al [25] found that most of the patients with HCM exhibited a reduction in left ventricular outflow tract obstruction with beta-blockers therapy treatment.…”
Section: Stress Echocardiography and Left Ventricular Outflow Tract Omentioning
confidence: 97%
“…There have been few developments in therapy since the last Almanac, but early prophylactic β-blocker therapy in physically active patients (NYHA 1 and 2) with provokable LVOTO has been shown to be effective in reducing outflow gradients during physiological exercise 17. Another study has confirmed the additive benefit of disopyramide in therapy of symptomatic patients with obstruction resistant to initial therapy with β-blocker or verapamil 18…”
Section: Hypertrophic Cardiomyopathymentioning
confidence: 99%